Enhanced Efficiency in Electric Vehicles: Gyroscopic Sensor for Power Optimization - Saurabh Ghadge; Omkar Salunkhe; Prathamesh Gadhave; P.V. Taware (International Journal of Optical Innovations & Research, 2024)
This research focuses on the design and production of a smart electric vehicle that uses a controlled gyroscopic sensor and microcontroller to automatically transfer power from the internal system to the wheels and vice versa. The era of electric vehicles has only recently begun, but it will significantly expand the automobile industry to the point where modern fossil fuel vehicles will eventually become outdated. The fact that they are environmentally friendly and thus produce fewer harmful emissions is what matters most. Electric vehicles (EVs) are gaining prominence due to advanced technologies that benefit both the industry and consumers. They utilize fewer sensors, miniaturized components, and contribute to reduced greenhouse gas emissions, thereby positively impacting both the power system and the environment. The project’s goal is to create a smart car that can switch its power transmission on its own. We measured the system’s slope angle using the gyroscope sensor for this purpose. We Designed PCB & used LED lights, an ESP32 with a Bluetooth module controller. Next, a comparative analysis between the experimental and analytical results will be conducted, and finally, a result and conclusion will be determined.
Keywords: Bluetooth module; ESP2; EV; Gyroscope Sensor etc; LED; PCB